Health-related quality of life outcomes between non-steroid and steroid aromatase inhibitors and switching hormone therapy in postmenopausal women with ER+ breast cancer - Wawang Anwarudin; Ajeng Diantini; Melisa I. Barliana; Auliya A. Suwantika (Pharmacia)
Adjuvant hormone therapy can affect the quality of life of postmenopausal breast cancer patients with the estrogen receptor (ER+). This study aimed to measure the outcomes of health-related quality of life (HRQoL) in postmenopausal women with ER+ breast cancer receiving non-steroidal aromatase inhibitors (NSAI), steroidal aromatase inhibitors (SAI), and hormone change therapy (Switch). This cross-sectional study was conducted by interviewing women with postmenopausal ER+ breast cancer. The EQ-5D-5L instrument was used to measure and compare utility scores among patients who received NSAI, SAI, and switch therapy. As a result, the average utility score EQ-5D-5L for NSAI is 0.864 (SD = 0.117), significantly different (p = 0.025) from SAI 0.777 (SD = 0.211) and switch 0.776 (SD = 0.071). The conclusion is that NSAI, SAI, and Switch significantly affected HRQoL in postmenopausal breast cancer patients with ER+. NSAI has a better quality of life compared to SAI and Switch.